2020
DOI: 10.1590/s1678-86212020000300435
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da composição granulométrica e da área superficial específica de resíduos de polimento de porcelanato em argamassas autoadensáveis

Abstract: Resumo O desenvolvimento de novas tecnologias e o incentivo ao reaproveitamento de resíduos vêm crescendo em função da redução dos prazos nas construções e da preocupação com o meio ambiente. O objetivo deste trabalho foi avaliar a influência da adição de resíduo de polimento de porcelanato (RPP) proveniente de dois lotes de uma empresa em argamassas autoadensáveis. Foram mantidos constantes a relação água/cimento e os teores de aditivos para cada porcentagem de adição de RPP. Observou-se que a granulometria e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Regarding finer granulometry aggregates (Aggregate 1), a higher percentage of absorption was observed in both aggregates (conventional and CDW). An increase in the specific area through the insertion of finer material contributes to this behavior, which ends up providing a larger surface for the physical absorption of water molecules [5,25]. This investigation revealed that compositions with smaller granulometry showed smaller bulk density as a result of the incorporation of finer and more porous particles.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Regarding finer granulometry aggregates (Aggregate 1), a higher percentage of absorption was observed in both aggregates (conventional and CDW). An increase in the specific area through the insertion of finer material contributes to this behavior, which ends up providing a larger surface for the physical absorption of water molecules [5,25]. This investigation revealed that compositions with smaller granulometry showed smaller bulk density as a result of the incorporation of finer and more porous particles.…”
Section: Resultsmentioning
confidence: 72%
“…Thus, there was more paste to surround the grains, reducing internal friction between the particles and increasing the flow [4]. As verified in the characterization of the aggregates, the granulometric composition that had a greater amount of fine particles (Aggregate 1) showed a larger specific area, providing a larger adsorption surface [5,25]. Therefore, when the water amount was kept constant, compositions with smaller granulometry tended to have a greater impact on workability, reducing the flow.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Ademais, é uma das poucas áreas industriais que pode obter vantagens no seu processo produtivo com a incorporação de resíduos entre suas matérias-primas, a exemplo da economia de matérias-primas de elevada qualidade, cada dia mais escassas e caras, a diversificação da oferta de matérias-primas, e a redução do consumo de energia e, por conseguinte, redução de custos. Esse potencial de incorporação de resíduos nas formulações de cerâmicas de revestimento, aliado às elevadas quantidades de recursos naturais consumidos a cada dia por esse segmento industrial, ressalta a importância da reutilização de resíduos como matérias-primas cerâmicas alternativas, racionalizando o uso dos recursos naturais [12,13].…”
Section: Introductionunclassified
“…Entretanto, não é comum encontrar estudos que avaliam a adição de mais de um resíduo simultaneamente. Através de buscas na literatura, observam-se pesquisas referentes à incorporação de uma variedade de resíduos, tais como: resíduos de polimento do porcelanato [2,13] lama de alto forno [14], pó de granito [15], cinza de lenha, lodo de estação de tratamento de água e cinza de casca de arroz [16], entre outros.…”
Section: Introductionunclassified